Policing the digital experience - Graham, Roderick (Cybercrime and digital deviance, 2024)
This chapter explores policing in the digital environment. The main topics covered consist of digital forensics, exploring data trails, and online undercover investigations. While the subject of such police work encompasses considerably more than these topics, they serve as an effective starting point for understanding the process, tools, challenges, and emerging trends in law enforcement of the digital experience. It is here that the reader is reminded of the underlying focus upon the individual’s experience online; laws and law enforcement practices rooted in the cybersecurity tradition - while relevant from a contextual perspective - are not the primary focus in this chapter. Rather, this chapter explores such material as how police officers prepare themselves to investigate cybercrimes, build cases against suspected digital offenders, track down those suspects and carry out arrest procedures. Here again, the reader is reminded that only that which is deemed criminally punishable under a law (e.g., local, state, or federal) is subject to police action; deviance alone is not. Accordingly, since laws can vary considerably state-to state and country-to-country, so too are the actions of law enforcement agencies dictated.